Policy, Practice, and Need in the Professional Preparation of Teachers for Rural Teaching - Ian W. Gibson (Journal of Research in Rural Education, 1994)
I analyze current policy and practice relating to the preparation and selection of teachers for rural areas of Australia and, in turn, contrast these to the corresponding perceptions of rural teachers. Conclusions are drawn regarding (a) the need for specialised preparation programmes for rural teachers and (b) the responsibility of education departments in the development of specific rural staffing policies and selection practices.